Android Based Groceries Shopping Application - H Purnomo; B C Arrahim; H A Dasuki; E S Nurhayati; N P Dewi (International Journal of Education, Information Technology, and Others, 2021)
The purpose of this study is to design an Android-based application to facilitate customers in shopping for groceries. To support this research, we used a descriptive method. The approach method we used is an object-oriented systems approach, while for the system development approach, we used the prototype method. In developing this grocery shopping application, several stages have been designed as a requirement so that an application can be structurally and well prepared. These stages are software requirements analysis, design, testing, and maintenance. The results achieved are a design of an Android-based grocery shopping application with a user-friendly interface and features. With this application, it is hoped that it will be easier for people looking for groceries during this pandemic of Covid-19. The application that we built can facilitate and increase online grocery shopping activities during the Covid-19 pandemic because the systems are integrated and automated. From our perspective, many aspects can be developed from designing this application in the future